2016
DOI: 10.1262/jrd.2016-058
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection-based generation of mutant mice with a double mutation and a 0.5 Mb deletion in their genome by the CRISPR/Cas9 system

Abstract: The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) system is a useful tool for genome editing. In this study, using a microinjection-based CRISPR/Cas9 system, we efficiently generated mouse lines carrying mutations at the Irx3 and Irx5 loci, which are located in close proximity on a chromosome and are functionally redundant. During the generation of Irx3/Irx5 double mutant mice, a deletion of ~0.5 Mb between the Irx3 and Irx5 loci was unintentionally identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
(27 reference statements)
2
21
0
Order By: Relevance
“…Correcting certain genetic disorders, such as T cell lymphomas, will require the introduction of two or more mutations in the same homologous chromosome (linked mutations) 30 , 31 . This can be achieved using base editing 32 but is more challenging to accomplish using nucleases such as Cas9, which introduce deletions or translocations of sequences between multiple cleavage sites 3 , 7 , 33 , and provoke undesired cellular responses to the presence of double-stranded breaks 7 , 8 , 34 , 35 . The remarkable rarity of proximal off-target mutations and the predominance of anticipated on-target and bystander edits in embryos exposed to ABE and to preferred CBE variants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Correcting certain genetic disorders, such as T cell lymphomas, will require the introduction of two or more mutations in the same homologous chromosome (linked mutations) 30 , 31 . This can be achieved using base editing 32 but is more challenging to accomplish using nucleases such as Cas9, which introduce deletions or translocations of sequences between multiple cleavage sites 3 , 7 , 33 , and provoke undesired cellular responses to the presence of double-stranded breaks 7 , 8 , 34 , 35 . The remarkable rarity of proximal off-target mutations and the predominance of anticipated on-target and bystander edits in embryos exposed to ABE and to preferred CBE variants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [30] reported a 95 kb deletion in mice. Recently, we demonstrated generation of mice carrying deletions of 0.5, 2, and 5 Mb and an inversion of 5 Mb [31,32]. To induce the 2 and the 5 Mb deletions, we microinjected Cas9/two sgRNAs and a donor plasmid carrying the breakpoint sequences so that the breakpoint sequence could be artificially defined.…”
Section: Reproduction Of Diseases In Mice Carrying Chromosome Rearranmentioning
confidence: 99%
“…In contrast, in the CRISPR-Cas9 system, the sgRNAs can share the same Cas9 nucleases, enabling the targeting of multiple genes in a single step by the injection of multiple sgRNAs with Cas9 nucleases into 1-cell embryos. Although these types of reports are currently limited (Table 1), [55][56][57][58][59][60][61] the simultaneous targeting of multiple genes by the CRISPR-Cas9 system is likely to become widely used for understanding complex genetic events.…”
Section: Multiplex Modificationmentioning
confidence: 99%